PENGARUH GREEN INVESTMENT DAN CSR INVESTMENT TERHADAP SUSTAINABLE PERFORMANCE: PERAN MEDIASI FINANCIAL PERFORMANCE: THE EFFECT GREEN INVESTMENT AND CSR INVESTMENT ON SUSTAINABLE PERFORMANCE: THE MEDIATING ROLE OF FINANCIAL PERFORMANCE - Puspitasari, Alifia Putri; Widoretno, Astrini Aning (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This study aims to analyze the factors that influence the sustainable performance of basic materials sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. This research method is descriptive quantitative.  The sample selection technique used purposive sampling technique so that a sample of 34 companies was obtained with a unit of analysis of 102 companies. The data analysis method uses path analysis. The results showed that green investment has no significant effect on financial performance or sustainability performance, because most companies make green investments only to fulfill regulations, not as a main business strategy. In contrast, CSR investment is proven to have a positive effect on financial performance and sustainability performance, because CSR can improve corporate reputation, stakeholder loyalty, and direct social and environmental impacts. Financial performance has no significant effect on sustainability performance and does not mediate the relationship between green investment and CSR investment with sustainability performance, indicating that sustainability requires a commitment that goes beyond economic aspects. The contribution of this research enriches the literature on sustainability in developing countries and provides input for the formulation of policies that support the effectiveness of CSR and green investment.